Nice and noir : contemporary American crime fiction - Schwartz, Richard B. (University of Missouri Press, 2002)
"Owners of mystery bookshops will tell you that there are several sorts of buyers: those who purchase on impulse or whim; genre addicts who buy paperbacks by the week and by the armful; and those who have caught up on canonical texts and regularly buy new novels by select authors in hardcover. Richard B. Schwartz belongs in the last group, with his own list of approximately seventy favorite writers." "Nice and Noir: Contemporary American Crime Fiction explores the work of these writers, building upon a reading of almost seven hundred novels from the 1980s and the 1990s. By looking at recurring themes in these msyteries, Schwartz offers readers new ways to approach the works in relation to contemporary cultural concerns." "Nice and Noir is wide-ranging but neither ponderous or lugubrious. Its language is accessible but not simplistic. The book will have a broad appeal - both to academics and to general readers with some interest in American studies and popular culture."--Jacket.